Tolerance to acute ischemia in adult male and female spontaneously hypertensive rats - Besík, J; Szárszoi, O; Kunes, J; Netuka, I; Malý, J; Kolár, F; Pirk, J; Ostádal, B (Physiological research, 2007)
Clinical and experimental studies have repeatedly indicated that overloaded hearts have a higher vulnerability to ischemia/reperfusion injury. The aim of the present study was to answer the question whether the degree of tolerance to oxygen deprivation in hearts of spontaneously hypertensive rats (SHR) may be sex-dependent. For this purpose, adult SHR and their normotensive control Wistar Kyoto (WKY) rats were used. The isolated hearts were perfused according to Langendorff at constant pressure (proportionally adjusted to the blood pressure in vivo). Recovery of contractile parameters (left ventricular systolic, diastolic and developed pressure as well as the peak rate of developed pressure) was measured during reperfusion after 20 min of global no-flow ischemia in 5 min intervals. Mean arterial blood pressure was measured by direct puncture of carotid artery under light ether anesthesia in a separate group of animals. The degree of hypertension was comparable in both sexes of SHR. The recovery of contractile functions in SHR males and females was significantly lower than in WKY rats during the whole investigated period. There was no sex difference in the recovery of WKY animals; on the other hand, the recovery was significantly better in SHR females than in SHR males. It may be concluded that the hearts of female SHR are more resistant to ischemia/reperfusion injury as compared with male SHR. This fact could have important clinical implications for the treatment of cardiovascular disease in women.
Keywords: reperfuzní poškození myokardu; potkani inbrední WKY; Male; hypertenze; Myocardial Reperfusion Injury; potkani inbrední SHR; mužské pohlaví; Hypertension; krysa rodu Rattus; Myocardial Contraction; Animals; krevní tlak; ženské pohlaví; zvířata; Rats; Blood Pressure; kontrakce myokardu; Rats, Inbred SHR; Female; Rats, Inbred WKY